The past and current state of the Czech outpatient electronic prescription (eRecept) - Bruthans, Jan (International journal of medical informatics, 2019)
INTRODUCTION: Outpatient Electronic Prescription Systems (OEPSs) are widely used in some European states, such as Denmark, Sweden and the Netherlands. The Czech OEPS (known as eRecept) was introduced in 2011, but with limited functions and voluntary usage it was not much accepted until 2018, when its usage was made compulsory not only for pharmacies, but for physicians as well. METHODS: Using data from the Czech State Institute for Drug Control (Státní ústav pro kontrolu léčiv or SÚKL in Czech) and from other sources, the system was described and data about its performance since 2013 have been obtained. RESULTS: The usage of the system was very low between 2013 and 2016, whilst moderate growth was seen in 2017. By 2018, the system has been widely adopted, although some twenty per cent of Czech physicians still do not use the system at all. DISCUSSION: A sudden rise in usage can be explained as the result of making the system compulsory starting in January 2018. Still, new features of the system are eagerly awaited and should be introduced to expand its benefits. CONCLUSION: The Czech Republic has joined the EU countries widely using the OEPS.
Keywords: Česká republika; pacienti ambulantní; Information system; Electronic Prescribing; Medication Errors; Czech Republic; Outpatients; Drug prescription; elektronické předepisování; lidé; medikační omyly; Humans; Electronic prescription